Managing the new customer relationship strategies to engage the social customer and build lasting value - Gordon, Ian 1952 June 19- (J. Wiley & Sons Canada, 2013)
Marketing has changed fundamentally in the last few years and has become an entirely new discipline, one that focuses on a new customer and a new relationship, framed by new principles, strategies, processes, roles and tactics. Individual customers are economically targeted and served, and treated as segments of one rather than members of a target market. Word of mouth and recommendations are vital as customers influence one another more than a company can do within its own advertising or customer dialogs. Today's customer is always online, accessible and connected. Now marketing is not only direct and customer-specific but a continuous process by which companies seek to engage customers and be progressively more relevant, attractive and valuable. This is the era of a new customer relationship an individual relationship that is social, mobile and local, influenced by peers and shaped by cognitive, behavioural and social psychological principles. New techniques, processes and technologies transform what it means to implement marketing strategy and achieve improved business results.
Includes bibliographical references and index
Keywords: Relationship marketing; Customer relations -- Management; Social media -- Marketing; Marketing relationnel; Customer relations; Management